The effect of uncertainty on negative discounting - Marcin Palenik (International Journal of Management and Economics, 2021)
The preference to receive benefits as early as possible and delay costs as much as possible is natural for people. That means a positive discount rate in the intertemporal choice, which is a common assumption in economics. However, as research in behavioral economics proves, in certain situations a negative discount rate occurs. The purpose of this paper is to show that the assumption of positive discounting is not always true. The presented experimental study shows how a decrease in probability increases the chances of negative discounting. According to the results, the expected large, uncertain profit is more likely to be deferred over time than a certain profit of the same value. On the other hand, the expected large, uncertain loss is more willingly experienced earlier than a certain loss of the same value. In both cases, it means an increase in the frequency of negative discounting due to increased uncertainty. The results of the study broaden the existing knowledge about the impact of probability on discounting in a situation of expected losses and the area of negative discounting.
Keywords: D15; D91; 650; behavioural economics; intertemporal choice; negative discounting; uncertainty